Pension provision of Kazakhstan: problems and perspectives - Zholdasbay, Zh. (International School of Economics KAZGUU, Nur-Sultan, 2022)
Pension provision for a certain category of the population is one of the priority directions of the social policy of any modern state. The background of this study is that the pension reform began in 1998 in Kazakhstan, which continues at this stage. During the years of independence, in difficult socio- economic and socio-political conditions, an independent pension system of the Republic of Kazakhstan has been formed, which is constantly being modernized taking into account the current socio-economic conditions. In this regard, it is important to understand the essence of the institutional pension reform, to determine the current principles of pension provision and the immediate prospects for the development of this institution. The paper analyzes the formation, development and current state of the independent pension system of the Republic of Kazakhstan. The chronological scope of the study covers the period from 1998 to 2021. The work is structured in the following areas: - the main directions of pension reform are identified and studied; the advantages and disadvantages of the existing pension system are structured; - the world practices of pension provision are considered; - the factors influencing the change in the state of the fund are identified; the directions of further development of the pension provision institute are determined. The methodological basis of the research is, first of all, the theoretical position of the general scientific systematization of complex processes (in this case, social), as well as the idea of the interconnectedness and interdependence between the identified factors that determine the development of the pension system. The general scientific principles used in this work include such methods as analysis and synthesis, induction and deduction, structural, historical, statistical and logical methods. The following main results should be highlighted: the classification of the reasons and conditions for the start of the pension reform is developed; the concept of the development mechanism and prospects for the development of the pension system is defined; the level of impact of such factors as the number of working-age population, the number of people of retirement age, average wages, etc.on the change in the fund is determined. The practical significance of the study lies in the fact that its results can be used for further study of social processes taking place in Kazakhstan
Keywords: Pension provision of Kazakhstan